No Gadget More Story, Gerakan Literasi Girimukti - Elok Yulia Widayanti; Cinta Wahyuning Suci; Stepanus Dedy Deomedes (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The problem of low reading interest among elementary school students is further exacerbated by the high use of gadgets, which often distract students from literacy activities. This situation prompted the implementation of the "No Gadget More Story" program as part of the Girimukti Literacy Movement, which aims to increase students' reading interest through reading and storytelling activities without the use of gadgets. This community service activity was carried out in several stages: preparation, implementation, evaluation, and reporting. Data collection techniques were conducted through observation, simple interviews, and documentation, then analyzed using qualitative descriptive analysis. The results showed that interactive reading and storytelling activities increased student engagement in literacy activities, fostered students' courage in retelling the story, and created a more active and enjoyable learning environment. These activities also helped reduce the distraction of gadget use during the learning process. This program also supports the optimization of the use of school libraries as learning spaces that support literacy development. Thus, the "No Gadget More Story" program can be an effective alternative literacy activity to foster a reading culture among elementary school students and has the potential to be developed sustainably within the school environment or through collaboration with village libraries.